Revenue Management Outsourcing: A Hybrid Model of Transaction Cost Economics and Organizational Capability - Altin, M.; Uysal, Muzaffer; Schwartz, Z. (2018)
Hotel revenue management is an activity domain that is uniquely technical, complex, and dynamic, and as such, it is often outsourced. This study explores the motivation of hotels to outsource their revenue management function to an outside entity. The major theoretical contribution is in being first to suggest, and empirically test, the notion that in complex environments, such as revenue management, the firm’s capabilities are moderating the impact of assets specificity on managers’ inclination to outsource. From a practical perspective, this study is the first to empirically explore the contextual determinants of the decision to outsource in the hotel-specific domain of revenue management.